KAJIAN DIGITALISASI PENDATAAN GROUND SUPPORT EQUIPMENT (GSE) GUNA MEMPERMUDAH PENGAWASAN UNIT AMC DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - zein indra utama; Nawang Kalbuana; Irwan Faizal (Ikatan Dosen Menulis, 2025)
In the era of digital transformation, optimizing airport operational monitoring systems has become a crucial need to enhance efficiency and safety. One essential aspect of ground operations is Ground Support Equipment (GSE), which ensures the smooth execution of aircraft activities on the ground. This study aims to evaluate the effectiveness of a digital-based GSE data collection system in supporting the monitoring performance of the Apron Movement Control (AMC) at Juanda International Airport, Surabaya. The research applied a descriptive qualitative approach through observation, interviews, and documentation techniques. The findings reveal that the existing manual system causes delayed data access, increases the risk of recording errors, and complicates the validation process of operational vehicle legality. Results also indicate that implementing digitalization via QR code-based applications, monitoring dashboards, and automatic notifications can accelerate decision-making processes, strengthen inter-unit coordination, and improve data accuracy and compliance with regulations. In conclusion, GSE digitalization significantly enhances AMC monitoring effectiveness and is highly recommended as a modern monitoring model for Indonesian airports.